Development Of Integrated Mathematics Learning Media In Islamic Values - Syafrita (Yana Research, 2022)
This study aims to: (1)Develop learning media for mathematics integrated with Islamic values ​​in trigonometry material for students, (2)Knowing the feasibility of learning media for mathematics integrated with Islamic values ​​in trigonometry material for students, (3)Knowing the effectiveness of the media Mathematics learning is integrated with Islamic values ​​in trigonometry material for students. This type of research is Research and Development (R&D) with the ADDIE research model consisting of five stages, namely analysis, design, development, implementation, and evaluation. The validation of learning media was carried out by material experts, media experts, and mathematics subject teachers. The developed media was tested on 37 students of class X MAN 1 Medan. The data analysis technique used is descriptive qualitative and quantitative descriptive techniques. The results of the research and development carried out are in the form of digital trigonometry comic learning media that can be accessed online through gadgets and computers. The developed media received good assessments from experts and teachers with an average feasibility score of 3.68 on a scale of 4 which was included in the very feasible category. In the field trial, students gave a good response with an average overall score of 3.65 on a scale of 4 which was included in the very feasible category. Then trigonometric comics are also effectively used in the learning process by obtaining an average score of 0.46 on the n-gain test which is included in the good category.